2021
DOI: 10.3390/microorganisms9112331
|View full text |Cite
|
Sign up to set email alerts
|

Structural-Dynamics and Binding Analysis of RBD from SARS-CoV-2 Variants of Concern (VOCs) and GRP78 Receptor Revealed Basis for Higher Infectivity

Abstract: Glucose-regulated protein 78 (GRP78) might be a receptor for SARS-CoV-2 to bind and enter the host cell. Recently reported mutations in the spike glycoprotein unique to the receptor-binding domain (RBD) of different variants might increase the binding and pathogenesis. However, it is still not known how these mutations affect the binding of RBD to GRP78. The current study provides a structural basis for the binding of GRP78 to the different variants, i.e., B.1.1.7, B.1.351, B.1.617, and P.1 (spike RBD), of SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
(77 reference statements)
1
7
0
Order By: Relevance
“…Together, the results presented in this study indicate that mutations that emerged in the new SARS-CoV-2 Omicron variant enhance the binding affinity of this variant to the host ACE2 receptor, which likely is an important driver of its increased transmissibility. However, it is important to note that SARS-CoV-2 besides ACE2 could also use other cellular receptors as a secondary binding way to target the host cells [19,[41][42][43]. Thus, it cannot be excluded that the changes that emerged in the Omicron viral spike could have an impact on the virus interaction with these secondary cellular receptors, additionally increasing the virus's ability to reach its target.…”
Section: Resultsmentioning
confidence: 99%
“…Together, the results presented in this study indicate that mutations that emerged in the new SARS-CoV-2 Omicron variant enhance the binding affinity of this variant to the host ACE2 receptor, which likely is an important driver of its increased transmissibility. However, it is important to note that SARS-CoV-2 besides ACE2 could also use other cellular receptors as a secondary binding way to target the host cells [19,[41][42][43]. Thus, it cannot be excluded that the changes that emerged in the Omicron viral spike could have an impact on the virus interaction with these secondary cellular receptors, additionally increasing the virus's ability to reach its target.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in virus empirical formulas lead to changes in Gibbs energy. As a rule, strains with greater infectivity are characterized by more negative Gibbs energy of binding ( Khan et al, 2021a , 2021b ). The results of this research are in agreement with those of Han et al, (2021) , who found that the difference in Gibbs energies of binding between Hu-1 and 501Y (ΔΔ B G ) is between 10.61 kJ/mol and 19.97 kJ/mol.…”
Section: Discussionmentioning
confidence: 99%
“…For the template the reported co-crystal PDB ID: 6M17 was considered. HADDOCK enabled restraint docking of the wild type and mutant was considering the previous parameter [13][14][15][16][17]. A special interface, Guru Interface, was exploited to exercise all the available options for best docking [10,[17][18][19][20].…”
Section: Structural Modeling and Interaction Predictionmentioning
confidence: 99%